Cenozoic structural development of the western flank of the Song Hong Basin, Gulf of Tonkin, Vietnam: Linking with onshore strike-slip faulting and regional tectonics. (1st May 2023) - Hoang, Bui H.; Fyhn, Michael B.W.; Hovikoski, Jussi; Boldreel, Lars O.; Tuan, Nguyen Q.; Dam, Mai H.; Long, Hoang V.; Tung, Nguyen T.; Nielsen, Lars H.; Abatzis, Ioannis
Graphical abstract: Highlights: Hue Sub-basin (HSB) is located in the western Song Hong Basin (SHB). HSB is distinct in structural development from SHB, despite earlier beliefs. The HSB opened in Late Oligocene – Early Miocene, driven by onshore strike-slip faults. Transpression in HSB and SHB might be resulted from SE Asia-Australia collision. Abstract: Cenozoic strike-slip deformation and associated basin formation in Indochina provide critical clues on crustal response during India-Asia collision. Typically, Indochina is considered a rigid block during continental extrusion. We demonstrate that the Song Ca-Rao Nay Fault System (SCRNFS) in north central Vietnam and its offshore extension, the Hue Sub-basin, subdivided Indochina into discrete blocks. Using an integrated dataset including topographic maps, geologic maps, onshore fieldworks, and offshore seismic and well interpretation, the structural evolution of the SCRNFS and Hue Sub-basin is investigated. During Late Oligocene, the SCRNFS initiated with right-lateral motion, causing pull-apart onshore and Hue Sub-basin opening offshore. The End-Oligocene inversion affecting the northern Song Hong Basin also caused a major NE–SW reverse fault in the Hue Sub-basin. In Early Miocene, rifting resumed in the Hue Sub-basin with accelerated faulting and westward rift migration in the south. This is distinct from the Song Hong Basin, where the main rift period was Eocene(?) – Oligocene, and the Early Miocene only features mild extension. During latest Early Miocene – earliest Middle Miocene, the SCRNFS switched to left-lateral transpression. This caused inversion and prolonged uplift in the northern-most Hue Sub-basin. The inversion associated unconformity can be traced onshore where it separates a compositionally immature conglomerate from an overlying quartz conglomerate. Left-lateral transpression in the Hue Sub-basin coincides with that in the Song Hong Basin and other inversion events across SE Asia. This may have been caused by Australia-SE Asia collision restricting escape movement of Indochina away from the India-Asia collision zone.